Verdade e Justiça: americanismo e fascismo nas histórias do Superman - Andreotti, Bruno Leonardo Ramos (2023)
The present work investigates the North American heroic imaginary based on the analysis of Superman comics throughout the 20th and early 21st centuries. These narratives are approached as constitutive elements of the imaginary as dimensions of history and, as such, producers of historically and socially constructed meanings, which give meaning to reality at the same time that they produce it. Through the analysis of the themes and images that compose and are repeated in these, referred to the context of their production, correlations are identified in the culture and social changes underlying the works, showing how these stories compose an Americanism and keep certain elements with fascism. Superman was born a child of the New Deal and Roosevelt, with a powerful motto: Truth, Justice and the American Way. Truth was brought by science, justice by due process of law, belief in institutions and the American Way was to help the needy and oppressed, then upholding law and order, and finally, on the eve of the United States' entry into World War II, defender of democracy. In the 50s and 60s, during the Cold War, the character's stories represent the fears and dreams of the United States in what was understood as a war not only against two antagonistic political and economic systems, but against antagonistic ways of life. It is during this period that the character crystallizes as a representative of optimism and the American Way. During the 1970s, there was a contestation of traditional American values. The character then begins to doubt himself, the importance and empowerment of his role. For the first time, a limit is placed on his actions, a moral, ethical limit: Superman can inspire humanity, but not govern it. As a counterpoint to this perspective, the Superman of the 1978 film emerges as a recovery of the vision of the 50s and 60s, with optimism and lost nostalgia and is acclaimed by the public. During the 80's the character's history is completely reformulated. Superman is more human than ever, imbued with American values in a neoliberal context where mass utopia has become detached from individual aspirations. This route is linked to the relationship between Americanism and fascism, revealing the paradox of the American heroic imaginary: the hero who acts to defend democratic institutions at the same time that his actions are anti-democratic, authoritarian